Farmers’ willingness to adopt digital application tools in Ogun State, Nigeria - Abioye, O.; Popoola, Olufemi; Akande, A.; Fadare, D.A.; Omitoyin, S.A.; Yinusa, B.; Kolade, O.O. (Emerald Publishing Limited, 2024)
Purpose